2013
DOI: 10.3390/ijms140816348
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Mitochondrial DNA Damage and Repair in the Resistance of BCR/ABL-Expressing Cells to Tyrosine Kinase Inhibitors

Abstract: Chronic myeloid leukemia (CML) is a hematological malignancy that arises from the transformation of stem hematopoietic cells by the fusion oncogene BCR/ABL and subsequent clonal expansion of BCR/ABL-positive progenitor leukemic cells. The BCR/ABL protein displays a constitutively increased tyrosine kinase activity that alters many regulatory pathways, leading to uncontrolled growth, impaired differentiation and increased resistance to apoptosis featured by leukemic cells. Current CML therapy is based on tyrosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 92 publications
(107 reference statements)
0
11
0
Order By: Relevance
“…The mitochondria and mtDNA are particularly susceptible to ROS-induced oxidative damage (Yakes and Van Houten, 1997) due to the fact that mtDNA lacks introns and undergoes transcription at a high rate (Glowacki et al, 2013). Mitochondrial enzymes are especially vulnerable to lipid peroxidation by peroxynitrite, leading to reduced ATP formation and induction of mitochondrial permeability transition via opening of the permeability transition pore, which dissipates the ΔΨ (Norenberg and Rao, 2007).…”
Section: Figure 10mentioning
confidence: 99%
“…The mitochondria and mtDNA are particularly susceptible to ROS-induced oxidative damage (Yakes and Van Houten, 1997) due to the fact that mtDNA lacks introns and undergoes transcription at a high rate (Glowacki et al, 2013). Mitochondrial enzymes are especially vulnerable to lipid peroxidation by peroxynitrite, leading to reduced ATP formation and induction of mitochondrial permeability transition via opening of the permeability transition pore, which dissipates the ΔΨ (Norenberg and Rao, 2007).…”
Section: Figure 10mentioning
confidence: 99%
“…4,9,10 Uncontrolled production of ROS can further damage/distract the mitochondrial membrane and its major constitutes like DNA, lipids, and proteins. 11 These fragments can initiate mitophagy to promote cell survival or can induce the initiation of the intrinsic pathway of apoptosis. 12,13 Initially, this condition can be regulated by mitochondrial fusion/fission activities.…”
Section: Introductionmentioning
confidence: 99%
“…Bcr/Abl has been shown to be the sole transforming oncogene in animal models of CML (Vicente-Dueñas et al, 2012) and is generally considered to be the causative agent in CML carcinogenesis (Zhou et al, 2017). Several prior studies have shown that Bcr/Abl can significantly inhibit apoptosis through effects on DNA damage and repair and can also mediate the resistance of tumor cells to multiple anticancer agents (Glowacki, Synowiec, & Blasiak, 2013). Therefore, targeting Bcr/Abl tyrosine activity to induce cell apoptosis and antiproliferation has been a promising approach for anti-CML drug development.…”
Section: Introductionmentioning
confidence: 99%